Scientific Mapping of Research Evolution on Innovative Pedagogy: A Bibliometric Analysis - Pal, Suman; Kumar, Vinod; Gangwar, Sumit (Journal of Data Science, Informetrics, and Citation Studies)
This Bibliometric investigation analyses the comprehensive research trends, publications, and citations over time frameworks, keyword occurrences, top productive authors, sources, and countries' research production on Innovative Pedagogy. For this study, the bibliometric analysis method was used. 4692 documents were extracted from the Scopus database published from 2000 to 2024 as of 9 September 2024 with the help of search keywords “Innovative Pedagogy” or "Innovative Pedagogies." The quantitative data analysis was conducted utilizing MS Excel (2021 version) and VOSViewer (1.6.20 version) software. The findings of this investigation indicated that the publications in the field of IP emerged before 2000; however, a significant surge was noted after 2010. Maximum publications (N=549) on IP were found in 2023. Similarly, the maximum number of citations (N=3622) was recorded in 2017. Nearly 55% of publications (N=2567) were Journal articles. The nations with the highest research output were the United States (N=1474), the United Kingdom (N=546), Australia (N=488), and India (N=214 Publications). The most productive author was Owolabi, O. A. (N=9 Publications), and the Institution was "Arizona State University, USA (13 Publications and 81 Citations). The most common keyword used in the IP domain was ‘teaching’ (699 occurrences, 14 links, and 1909 total link strength). This paper will be helpful for the scientific community as well as novel researchers. This paper provides a global lens on Innovative Pedagogy related publications.
Keywords: Innovative Pedagogy; Bibliometrics; Keyword Trends; Research Evolution; Scientific Visualization; VOSViewer.